2019
DOI: 10.2147/tcrm.s198735
|View full text |Cite
|
Sign up to set email alerts
|

<p>The accuracy assessment of presepsin (sCD14-ST) for mortality prediction in adult patients with sepsis and a head-to-head comparison to PCT: a meta-analysis</p>

Abstract: Objective: The soluble cluster of differentiation 14 subtype (sCD14-ST) or presepsin has recently been identified as a promising biomarker in sepsis. The present meta-analysis is performed to assess the prognostic value of presepsin in septic patients. Further, we compare the prognostic performance between presepsin and procalcitonin (PCT) in predicting all-cause mortality in these patients. Methods: A systemic and comprehensive search was conducted in PubMed, Embase and Coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 61 publications
(81 reference statements)
3
22
1
2
Order By: Relevance
“…A meta-analysis ( 30 ) including 23 studies with 3994 patients found that elevated PCT levels were associated with a higher risk for death. Nevertheless, a recently published study ( 31 ) also found that PCT was a promising biomarker for the prognosis of mortality in sepsis, with an AUROC of 0.81, which was higher than our results. This may be attributed to patient selection and PCT testing time.…”
Section: Discussioncontrasting
confidence: 96%
“…A meta-analysis ( 30 ) including 23 studies with 3994 patients found that elevated PCT levels were associated with a higher risk for death. Nevertheless, a recently published study ( 31 ) also found that PCT was a promising biomarker for the prognosis of mortality in sepsis, with an AUROC of 0.81, which was higher than our results. This may be attributed to patient selection and PCT testing time.…”
Section: Discussioncontrasting
confidence: 96%
“…On the other hand, although CRP is widely used in the critical care setting and its value as a prognostic and predictor marker is proven in many diseases including sepsis, the levels of CRP in the current study could not predict the mortality in the studied septic patients. Such findings agreed with others who reported that the initial CRP values did not predict mortality in septic ICU patients [35,41].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, no significant difference in CRP levels existed between the two subgroups. Such results agreed with the another study which demonstrated that the PCT and presepsin levels were good parameters for reflecting the severity of sepsis [21] On the contrary, Ulla et al reported no differences in the presepsin levels between the sepsis and septic shock groups, and Zhu et al showed no significant association between the level of PCT and the grade of sepsis [34,35].…”
Section: Discussionsupporting
confidence: 89%
“…Also in this regard, research and innovation would benefit from greater knowledge, skills and use of bioinformatics, epigenetics 9 and new biomarkers, such as presepsin. 10…”
Section: Challengesmentioning
confidence: 99%